Legal Protection for Children in Conflict with the Law: Process and Problems - Prabasini, Olif Skear (The Indonesian Journal of International Clinical Legal Education, 2021)
The implementation of coaching prisoners, whether male, child or female, in an effort to return prisoners to a good society, is very important, not only material or spiritual, but both must run in balance, these are the main things that support prisoners easily in living their lives. after serving the sentence. Guidance in Correctional Institutions is expected to be able to shape the personality and mentality of prisoners who are considered not good in the eyes of the community to become normal and in accordance with applicable norms and laws Real efforts to guarantee the basic rights of women. The purpose of this study is to determine the rights of a child in obtaining legal assistance, to find out and analyze regulations regarding children, and to analyze the mechanism of legal protection for children who are in conflict with the law.